2002
DOI: 10.1042/bj20011854
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyl transpeptidase expression in Ewing's sarcoma cells:up-regulation by interferons

Abstract: The genetic hallmark of Ewing's sarcoma family of tumours (ET) is the presence of the translocation t(11;22)(q24;q12), which creates the ET fusion gene, leading to cellular transformation. Five human gamma-glutamyl transpeptidase (gamma-GT) genes are located near the chromosomal translocation in ET. gamma-GT is a major enzyme involved in glutathione homoeostasis. Five human cell lines representative of primary or metastatic tumours were investigated to study whether gamma-GT alterations could occur at the chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…27 Moreover, there is increasing evidence indicating that systemic inflammatory response plays an important role in cancer progression. 28 Our data showed that ALB and GGT are predictors for patients with HCC after curative hepatectomy over a long-term followup, and revealed that preoperative decreased ALB levels and elevated GGT levels were significantly associated with shorter OS and RFS.…”
Section: Discussionmentioning
confidence: 51%
“…27 Moreover, there is increasing evidence indicating that systemic inflammatory response plays an important role in cancer progression. 28 Our data showed that ALB and GGT are predictors for patients with HCC after curative hepatectomy over a long-term followup, and revealed that preoperative decreased ALB levels and elevated GGT levels were significantly associated with shorter OS and RFS.…”
Section: Discussionmentioning
confidence: 51%
“…The pro-oxidant reactions produced by GGT could supplement endogenous Reactive oxygen species (ROS) in cancer cells, and endogenous ROS can contribute to the ‘persistent oxidative stress’, which is described as a factor in genomic instability and carcinogenesis [ 42 ]. Furthermore, a great number of cytokines including tumor necrosis factor alpha (TNF-alpha) [ 43 ], and interferon (IFN)-alpha and -beta [ 44 ], could induce GGT mRNA expression. These results indicate a connection between inflammation and GGT expression, not just as a response to inflammation-related oxidative stress, but rather as the effect of specific inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…High GGT levels may lead to liver dysfunction via inducing DNA instability, tumorigenesis and cancer progression. In addition, high GGT levels can predict the poor prognosis of HCC [49,50] High AFP levels indicate that the tumor is highly aggressive as well as the probability of intra-hepatic metastasis being usually greater than in patients with low AFP levels [51]. Other studies have repeatedly reported that a larger tumour diameter is signi cantly associated with PHER [52] and that MVI, satellite nodules and tumor differentiation are related to worse PHER [53][54][55].…”
Section: Discussionmentioning
confidence: 99%